The Consumer Behaviour of Taiwanese Young People: With Respect to Luxury Brand Products - Li, Wei-Hsuan (2006)
In recent years, there is a fever of buying and using luxury brand products in Taiwanese young generation. Young people are feverish to purchase expensive and luxury goods from those famous international luxury brands. This dissertation aims to investigate this phenomenon in depth.